Proposal for standardization of the distance for analysis of freestyle flip-turn performance - Silveira, G. A.; Gassenferth Araujo, L.; dos Santos Freitas, E.; Schütz, G. R.; Gonsaga de Souza, T.; Matheus Pereira, S.; Roesler, H. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2011)
The ongoing research on freestyle flip turns requires the standardization of assessment methods and protocols. The objective of this study was to propose a standardization of the distance used for the analysis of flip-turn performance. Eleven swimmers of both genders (16±3 years) participated in the study. Peak force (PF) and contact time (CT) were measured using a force platform. Five camcorders were installed to determine the flip-turn time at a distance of 15 (TT15) and 10 m (TT10), distance before the turn, distance to regain stroke, and time without stroke. Each swimmer performed eight flip turns. The level of significance was set at p<0.01. Mean PF was 1075 N and mean CT was 0.32 s. Mean TT10 and TT15 were 5.52 and 8.81 s, respectively. PF and CT were associated with flip-turn performance at distances of 10 and 15 m. However, this association was stronger when analyzing time without stroke, which is part of the flip-turn phases. In conclusion, PF and CT were associated with flip-turn performance at distances of 10 and 15 m. A distance of 10 m was found to be sufficient to evaluate athletes with technical characteristics similar to those of this study. The use of the 15-m distance is recommended for swimmers with different technical characteristics, such as a longer underwater phase.